Effects of Climate Change on Avalanche Accidents and Survival - Strapazzon, Giacomo; Schweizer, Jürg; Chiambretti, Igor; Brodmann Maeder, Monika; Brugger, Hermann; Zafren, Ken (Frontiers in Physiology, 2021)
Avalanches are a major natural hazard in snow covered mountains, threatening people and infrastructure. With ongoing climate change, the frequency and types of snow avalanches may change, affecting the rates of avalanche burial and survival. In this review we assess the potential effects of climate change on the frequency and characteristics of avalanches. We then discuss how these changes might affect the survival rates of subjects buried by avalanches and might influence the responses of search and rescue (SAR) teams and health care providers. While climate change is inevitable, the effects on avalanches remain elusive. The frequency of human triggered avalanches may not change, because this depends largely on the number and behavior of winter recreationists. Blunt trauma and secondary injuries will likely become more frequent as terrain roughness is expected to rise and snow cover to become thinner. Higher snow densities in avalanche debris will likely interfere with the respiration of completely buried victims. Asphyxia and trauma, as causes of avalanche death, may increase. It is unlikely that SAR and health care providers involved in avalanche rescue will have to change their strategies in areas where they are already established. The effects of climate change might foster the expansion of mitigation strategies and the establishment of mountain rescue services in areas subject to increased avalanche hazards caused by changes in snow cover and land use.